Extraction, characterization, and biological toxicity of β-glucans from Saccharomyces cerevisiae isolated from ragi - Indriati Ramadhani; Diva Larissa; Yeni Yuliani; Mellova Amir; Kusmiati Kusmiati (Journal of Microbial Systematics and Biotechnology, 2020)
β-glucan is a homopolysaccharide with biological activities that are beneficial to health as an immunostimulant, anti-inflammatory, anti-diabetic, anti-cholesterol, and many more. β-glucan extraction results from yeast require characterization related to this bioactive quality, such as β-glucan weight, monomer analysis, functional groups, and cytotoxicity assay. Four Saccharomyces cerevisiae isolates were isolated from three local ragi samples, namely the SC-1, SC-2, SC-3, and SAF from instant ragi. This study aimed to obtain the best candidate of S. cerevisiae isolates to produce high β-glucan levels and low protein levels and to test the potential for cytotoxicity. The four isolates were rejuvenated on potato dextrose agar (PDA), then inoculated into the liquid glucose yeast peptone (GYP) fermentation medium for six days. Saccharomyces cerevisiae cells were extracted by neutralizing acid-base, dried and weighed as a crude β-glucan (mg per 300 mL). The highest yield was SC-2 (818 mg), followed by SC-3 (726 mg), SAF (597 mg), and SC-1 (433 mg). The presence of –OH (alcohol), -C-C-C- (alkane), and –R-O-R- (ether) groups were showed using FTIR characterization. Glucose equivalent β-glucan levels and protein levels were determined using a UV-Vis spectrophotometer. The results showed that β-glucan SC-1 gave the best results with glucose equivalent β-glucan levels of 4,865% and protein levels of 3,804%. The crude β-glucan toxicity test using the brine shrimp lethality test (BSLT) method shows that the β-glucan of the SAF strain has LC50 cytotoxicity of 114.8 ppm followed by β-glucan cytotoxicity from local ragi LC50 was SC-2 (323.5 ppm), SC-1 (331.1 ppm), and SC-3 (354.8 ppm). Therefore, based on the results, SC-1 isolate obtained the highest β-glucan crude and the lowest protein content was SC-2. The β-glucan of SAF extract had the highest toxicity properties based on the IC50 value.